Endophytic Paenibacillus polymyxa LMG27872 inhibits Meloidogyne incognita parasitism, promoting tomato growth through a dose-dependent effect - Singh, Richard Raj; Wesemael, Wim M. L. (Frontiers in Plant Science, 2022)
The root-knot nematode Meloidogyne incognita is a major pest in tomato production. Paenibacillus polymyxa is primarily found in soil and colonizing roots, being considered a successful biocontrol organism against many pathogens. To evaluate the biocontrol capacity of P. polymyxa LMG27872 against M. incognita in tomato, experiments were conducted both in vitro and in vivo. A dose-response effect [30%, 50% and 100% (108 CFU/mL)] of bacterial suspensions (BS) on growth and tomato susceptibility to M. incognita with soil drenching as a mode of application was first evaluated. The results show that the biological efficacy of P. polymyxa LMG27872 on M. incognita parasitism in tomato was dose-dependent. Significantly reduced number of galls, egg laying females and number of second-stage juveniles (J2) were observed in BS-treated plants, in a dose dependent manner. The effect of P. polymyxa on tomato growth was also dose dependent. High dose of BS had a negative effect on growth, however this negative effect was not observed when these BS-treated plants were challenged with M. incognita, indicating tolerance or a defense priming mechanism. In subsequent in vivo experiments, the direct effect of BS was evaluated on J2 mortality and egg hatching of M. incognita. The effect of BS on J2 mortality was observed from 12 to 24 hrs whereby M. incognita J2 were significantly inhibited by the BS treatment. The effect of P. polymyxa on M. incognita egg hatching was also dependent on BS dose. The results show a potential of P. polymyxa LMG27872 to protect plants from nematode parasitism and its implementation in integrated nematode management suitable for organic productions.